Educational Activity and The Essence of Its Activation (Journal of Pedagogical Inventions and Practices, 2023)
the article is devoted to the systematic organization of the process of activating educational and cognitive activities in higher pedagogical education, which allows to change the methods and technologies of increasing the activity of educational and cognitive activities of students, the systematic organization of the process of activating educational and cognitive activities, the use of interactive forms and methods, and the teacher's activity It is a targeted activity aimed at improving the system of knowledge and educational tools in order to change, improve professional skills, strengthen the student's practical orientation, arouse interest in the acquisition and practical application of knowledge in students, increase their activity, creativity, and independence, and is the direction of student activity to improve existing knowledge and search for new knowledge, the actions of the teacher in the process of higher education aimed at optimizing education, developing voluntary efforts in the process of acquiring knowledge, abilities and skills, coordinating the actions of all mental processes and situations, reflecting the nature of the needs, motives, interests, abilities, assessments and emotional state of higher education subjects is an integral system of conscious, individual communication with various aspects of education and knowledge, which reveals the content of ensuring the success of the process and results of acquiring knowledge in science